2022
DOI: 10.12688/wellcomeopenres.18016.2
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease (CKD) and associated risk in rural South Africa: a population-based cohort study

Abstract: Background: In Africa, true prevalence of chronic kidney disease (CKD) is unknown, and associated clinical and genetic risk factors remain understudied. This population-based cohort study aimed to investigate CKD prevalence and associated risk factors in rural South Africa. Methods: A total 2021 adults aged 20-79 years were recruited between 2017-2018 from the Agincourt Health and Socio-Demographic Surveillance System in Bushbuckridge, Mpumalanga, South Africa. The following were collected: sociodemographic, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…[52][53][54] In a South African study, where CKDu made up 32% of the CKD burden, the APOL1 gene risk variants were associated with a 2-fold risk of CKD. 43 In this setting, lack of association of APOL1 risk variants with hypertension attributed CKD was also reported. 55 In a population-based study in Nigeria, the APOL1 risk variants were associated with an almost 5-fold risk of CKD of nondiabetic aetiology after adjustment for gender, age, body mass index and HIV, a proxy for CKDu.…”
Section: Ckd and Genetic Factorsmentioning
confidence: 90%
See 3 more Smart Citations
“…[52][53][54] In a South African study, where CKDu made up 32% of the CKD burden, the APOL1 gene risk variants were associated with a 2-fold risk of CKD. 43 In this setting, lack of association of APOL1 risk variants with hypertension attributed CKD was also reported. 55 In a population-based study in Nigeria, the APOL1 risk variants were associated with an almost 5-fold risk of CKD of nondiabetic aetiology after adjustment for gender, age, body mass index and HIV, a proxy for CKDu.…”
Section: Ckd and Genetic Factorsmentioning
confidence: 90%
“…Due to the lack of attention and poor focus on the condition, many studies just reported CKD with no diabetes, hypertension or HIV. [42][43][44][45][46][47][48] Though the use of different criteria (Table 1) is a limitation on comparison of these findings and may lead to inadequate capture of CKDu cases, they are still informative about the burden of CKDu in African countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…
The burden of end-stage kidney disease (ESKD) continues to increase worldwide. The prevalence of chronic kidney disease (CKD) in South Africa (SA) is estimated to range from 6% to 17% [1][2][3] and is predicted to worsen in the future, for several reasons. [4][5][6][7] Despite being considered an upper middle-income country, [8] SA is ranked as the most unequal country in the world, with a Gini index of 63.
…”
mentioning
confidence: 99%